Assessment of early life stage mahi‐mahi windows of sensitivity during acute exposures to Deepwater Horizon crude oil. (2nd February 2017) - Mager, Edward M.; Pasparakis, Christina; Schlenker, Lela S.; Yao, Zongli; Bodinier, Charlotte; Stieglitz, John D.; Hoenig, Ronald; Morris, Jeffrey M.; Benetti, Daniel D.; Grosell, Martin
Abstract: Windows of exposure to a weathered Deepwater Horizon oil sample (slick A) were examined for early life stage mahi‐mahi ( Coryphaena hippurus ) to determine whether there are developmental periods of enhanced sensitivity during the course of a standard 96‐h bioassay. Survival was assessed at 96 h following oil exposures ranging from 2 h to 96 h and targeting 3 general periods of development, namely the prehatch phase, the period surrounding hatch, and the posthatch phase. In addition, 3 different oil preparations were used: high‐ and low‐energy water accommodated fractions of oil and very thin surface slicks of oil (∼1 μm). The latter 2 were used to distinguish between effects due to direct contact with the slick itself and the water underlying the slick. Considering the data from all 3 exposure regimes, it was determined that the period near or including hatch was likely the most sensitive. Furthermore, toxicity was not enhanced by direct contact with slick oil. These findings are environmentally relevant given that the concentrations of polycyclic aromatic hydrocarbons eliciting mortality from exposures during the sensitive periods of development were below or near concentrations measured during the active spill phase. Environ Toxicol Chem 2017;36:1887–1895. © 2016 SETAC